The Pattern of Parental Assistance in the Pandemic Era in Surabaya Elementary Schools - Ariyanti, Lita (International Conference on Elementary Education, 2022)
Covid-19 is a virus that originated in Wuhan, China. The first case of covid-19 was announced by President Jokowi in March 2020 and the Indonesian state began to slowly change, all activities were stopped including learning. Schools began to stop activities and create a new learning tradition, namely online learning. Unexpectedly, it turns out that online learning even though there is a positive impact, there is also a negative impact which makes it difficult for teachers to give lessons, not only teachers, parents also have difficulty in guiding and directing their children to do online learning. This study aims to determine the pattern of mentoring carried out by parents in public and private elementary schools, especially in the big city, Surabaya. The data obtained using a questionnaire using the google form platform that was selected randomly. The results of this study found that some parents who certainly did not work to accompany their children to the maximum even though it was difficult to guide and direct, and some parents trusted their eldest child, the tutor to accompany online learning. The conclusion of this study is that parents find it difficult to accompany their children in online learning, they hope that online learning can be done offline or face to face.